Enolase of Staphylococcus lugdunensis Is a Surface-Exposed Moonlighting Protein That Binds to Extracellular Matrix and the Plasminogen/Plasmin System - Hussain, Muzaffar; Kohler, Christian; Becker, Karsten (Frontiers in Microbiology, 2022)
The coagulase-negative staphylococcal (CoNS) species Staphylococcus lugdunensis is unique in causing serious infections in humans that resemble those of Staphylococcus aureus rather than those of other CoNS species. The colonisation and invasion of host tissue presupposes the presence of adherence factors, but only a few proteins mediating adhesion of S. lugdunensis to biotic surfaces are known yet. Here, we report on the functionality of the S. lugdunensis enolase (SlEno) which performs two distinct roles, first as the metabolic enzyme of the glycolysis and second as an adherence factor to the extracellular matrix (ECM) of cells. Phylogenetic analyses of the SlEno confirmed their high conservation to enolases of other species and revealed a closer relationship to Staphylococcus epidermidis than to S. aureus. Using matrix-assisted laser desorption/ionization time of flight mass spectrometry and Western-Blot experiments, we identified SlEno to be located in the cytoplasm as well as on the cell surface of S. lugdunensis. Recombinantly generated and surface-associated SlEno showed the usual enolase activity by catalyzing the conversion of 2-phosphoglycerate to phosphoenolpyruvate, but, in addition, also displayed strong binding to immobilized laminin, fibronectin, fibrinogen and collagen type IV in a dose-dependent manner. We also showed a strong binding of SlEno to plasminogen (Plg) and observed a tissue plasminogen activator (tPA)-dependent conversion of Plg to plasmin (Pln) whereby the Plg activation significantly increased in the presence of SlEno. This interaction might be dependent on lysines of the SlEno protein as binding to Plg was inhibited by ɛ-aminocaproic acid. Furthermore, the enhanced activation of the Plg/Pln system by SlEno enabled S. lugdunensis to migrate through a fibrin matrix. This migration was about 10-fold higher than without exogenously added SlEno. Finally, we observed a significantly higher clearance of S. lugdunensis by freshly prepared granulocytes and in the presence of anti-SlEno antibodies. In conclusion, these data demonstrate for the first time a moonlighting function of the S. lugdunensis enolase, which is an underrated virulence factor for colonization and invasion of tissues. Hence, SlEno might be a potential vaccine candidate to prevent severe infections caused by this pathogen.